Teaching Music Composition: A Poetic Interdisciplinary Path Through Art and Life - Yampolschi, Roseane (Revista Vórtex, 2020)
In this essay I introduce some ideas and experiences that have been the object of numerous studies and resource materials for composition for several years. This whole information has to do, firstly, with an interdisciplinary context of studies and music creation that refers back to my doctoral thesis; secondly, with research and creative experiences based on the musical gesture and that one under the perspective of "enactment" ; and thirdly, with a poetic view of the sonorous architecture of the artistic work from an intrinsic relation between sound and silence.